The effect of usage of Artemisia herba alba and Urtica dioica herbs extracts on the histopathological changes of Eimeria tenella parasite in the broiler chick.: Dunia Abid-AlMalik , Haider Mohammad Ali Al-Rubaie and Enam Bader Falih - Ali Al-Rubaie1, Haider Mohammad (The Iraqi Journal of Veterinary Medicine, 2012)
This study was conducted to determine the biological effects of both Artemisia herba alba andUrtica dioica on the pathogenesis of Eimeria tenella, so 150 broilers, 7days old (Ross breed)were used, divided randomly into 6 groups. The first fourth groups include 30 chicks for eachgroup, while fifth and sixth groups have 15 chicks for each, consider as positive and negativegroups.The first five groups infected orally with 1000 oocysts of E.tenella directly into the cropat 17 days old. Histopathological examination of cecae in the treated groups with Urtica dioicarevealed moderate mononuclear cells (MNCs) infiltration, while sever lymphocytic aggregationswere seen in the treated group of water extract comparing with less cellular inflammatoryinfiltration was seen in the treated group with Artemisia herba alba .Severe degeneration andnecrotic changes were appeared in epithelial layer of mucus glands as well as appearance ofdegenerated schizonts in the section of the control group.